THE EQUIVALENCE OF BERTRAND EQUILIBRIUM IN A DIFFERENTIATED DUOPOLY AND COURNOT EQUILIBRIUM IN A DIFFERENTIATED OLIGOPOLY - LEE, DongJoon; HAN, Sangheon; ONO, Yuji; OH, Joonghwa (Theoretical and Practical Research in Economic Fields, 2016)
This paper examines whether Bertrand equilibrium in a differentiated duopoly can be duplicated with Cournot competition or not. We show that the degree of product differentiation plays an important role in the duality between those equilibria. Our main claims are two. One is that there exists a unique duality condition that satisfies the equivalence between Bertrand and Cournot equilibrium irrespectively of market structures. The other is that the number of firms of Cournot competition that satisfies Bertrand equilibrium increases with the degree of product differentiation.